STUDI PEMANFAATAN LIMBAH ABU TERBANG BATUBARA (FLY ASH) DAN ALUMINIUM DAUR ULANG SEBAGAI PENGGANTI MATERIAL BANTALAN LUNCUR - Surya, Rayana Djaka; Taufikurahman, Taufikurahman; Sundari, Ella (MACHINERY Jurnal Teknologi Terapan, 2020)
Aluminium is a soft metal with an attractive appearance, light weight and corrosion resistance. In this study, canned aluminium waste as a matrix and fly ash waste as reinforcement. In making specimens through a casting process using the casting method with a temperature of 7000C. The results of this study, the highest hardness value in the variation of alloy AL 60%: FA 40% at 82,726 kg/mm2 with the lowest hardness level at variation AL 100%: 0% FA at 60,036 kg/mm2 and the highest impact value on AL 100% : FA 0% at 0.0167 J/mm2 with the lowest impact value on the variation AL 60%: FA 40% at 0.0113 J/mm2. From these results it is known that the more weight fraction of fly ash is added to the aluminum, the level of hardness increases and this result is inversely proportional to the impact value because the higher the hardness value of a material, the more brittle the material is. So it can be concluded that canned aluminum waste material and coal fly ash are suitable to be used as a substitute for the sliding bearing material.